2005
DOI: 10.1159/000086471
|View full text |Cite
|
Sign up to set email alerts
|

Pharmacological and Functional Characterization of Endothelin Receptors in Bovine Trabecular Meshwork and Ciliary Muscle

Abstract: To clarify the potential role of endothelin-1 (ET-1) in the pathogenesis of glaucoma, the endothelin receptors expressed in bovine trabecular meshwork (TM) and ciliary muscle (CM) were identified. TM and CM strips were subjected to ET-1 as well as to specific endothelin receptor antagonists. In both tissues BQ123, a specific ET-A receptor antagonist, substantially inhibited ET-1-induced contraction. BQ788, a specific ET-B receptor antagonist, showed only moderate effects. Both ET receptor types were detected i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
14
0
1

Year Published

2007
2007
2019
2019

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 20 publications
(17 citation statements)
references
References 54 publications
2
14
0
1
Order By: Relevance
“…ET-1 Ca 2+ -independent contraction seems to be mediated both by ET-AR and ET-BR, since specific inhibitors for each receptor lead to decreased responses but not to a complete abolishment of TM contractility. Choritz et al reported almost no alteration in ET-1-induced BTM contraction after incubation with the ET-BR specific antagonist BQ788, suggesting that this receptor should not contribute to ET-1 contraction of BTM in the presence of Ca 2+ [17]. In a condition of Ca 2+ -depletion, even if ET-AR inhibition had a greater effect on BTM contractility, we were able to demonstrate an ET-1-induced contraction mediated by ET-BR.…”
Section: Discussionsupporting
confidence: 42%
See 1 more Smart Citation
“…ET-1 Ca 2+ -independent contraction seems to be mediated both by ET-AR and ET-BR, since specific inhibitors for each receptor lead to decreased responses but not to a complete abolishment of TM contractility. Choritz et al reported almost no alteration in ET-1-induced BTM contraction after incubation with the ET-BR specific antagonist BQ788, suggesting that this receptor should not contribute to ET-1 contraction of BTM in the presence of Ca 2+ [17]. In a condition of Ca 2+ -depletion, even if ET-AR inhibition had a greater effect on BTM contractility, we were able to demonstrate an ET-1-induced contraction mediated by ET-BR.…”
Section: Discussionsupporting
confidence: 42%
“…Both ET receptors ET-AR and ET-BR have been shown to occur in this tissue in bovine and human studies [16][17][18]. ET-receptors are also expressed in ciliary muscle, and both bovine CM and TM contract when exposed to ET-1 (for a review, see [4]).…”
Section: Discussionmentioning
confidence: 99%
“…EG-1 is capable of causing contraction of TM and, thus, a decrease in the intertrabecular space with an increase in the resistance of the intraocular fluid outflow. EG-1 also causes contraction of the ciliary muscle and tension on the TM [22]. Since the elucidation that TM and ciliary body express both receptor subtypes for ET-1 and that EG-1 is present in the intraocular fluid, it has been suggested that ET-1 has influence on the IOP by affecting the balance between the functionally antagonistic contractile forces of these tissues.…”
Section: Introductionmentioning
confidence: 99%
“…A mechanism of control on IOP has also been considered, namely inhibition of the Na + /K + -ATPase in the non-pigmented ciliary epithelial cells in cultures. In vivo this could mean decreased production of intraocular fluid and, hence, a decrease of IOP [22].…”
Section: Introductionmentioning
confidence: 99%
“…The following ET-1-induced contraction in the presence of BQ-123 was strongly reduced, whereas BQ-788 has no effect. (B) Expression of endothelin receptors verified with Western blot analysis in cultured cells of bovine and human trabecular meshwork (modified from Choritz et al, 2005;Copyright S. Karger AG, Basel;Rosenthal et al, 2007).…”
Section: Figurementioning
confidence: 99%